Novel FUS mutation Y526F causing rapidly progressive familial amyotrophic lateral sclerosis. Issue 1 (2nd January 2021) - Zou, Zhang-Yu; Che, Chun-Hui; Feng, Shu-Yan; Fang, Xiu-Ying; Huang, Hua-Pin; Liu, Chang-Yun
Abstract: FUS gene is one of the most common mutated genes in amyotrophic lateral sclerosis (ALS). We sequenced for FUS mutations in a cohort of 15 familial ALS and 275 sporadic ALS of Chinese origin. All 15 exons of the FUS gene were sequenced by targeted next-generation sequencing in a cohort of 15 familial ALS indexes and 275 sporadic ALS patients of Chinese origin. One novel p.Y526F mutation in FUS was detected in one familial ALS proband. Another novel FUS p.Q140R variant and two known FUS mutations (p.R495Efs*33 and p.R521C) were identified in four sporadic ALS cases. The frequency of FUS mutation in our cohort is 6.7% in familial ALS and 1.5% in sporadic ALS. The familial ALS proband carrying the FUS p.Y526F mutation presented with juvenile-onset lower limbs weakness and demonstrated an aggressive course, with respiratory muscles involvement 6 months after onset. The other patients in the family all had limbs weakness and died 1–2 years after disease onset. Our results strengthen that FUS mutations are the most frequent genetic causes of young-onset aggressive ALS. Genetic testing of the FUS gene should be performed in early-onset ALS patients especially those with a rapid progression.